Sexuality in chronic respiratory failure: coincidences and divergences between patient and primary caregiver (2001)
Sexual functioning can be affected by chronic illness in a variety of ways. These problems affect the patient's relationship and the degree of satisfaction with his partner. We conducted a study in order to evaluate the perception of sexual difficulties and changes in communication with patients and their wives. Male chronic obstructive pulmonary disease patients with (COPD) and chronic respiratory failure on long-term oxygen therapy were studied. The evaluation method used has consisted of the individualized administration of a semi-structured interview created for this purpose. This interview was conducted with the patients and their wives. One part of the interview was dedicated to evaluating possible sexual problems and how these problems affect the relationship between the couples. In addition, patients as well as their partners were asked the degree of satisfaction with their partners and the degree of satisfaction with their lives. Forty-nine patients and their spouses have been included in the study. Thirty-three patients (67·3%) showed some type of sexual problem (lack of desire and/or impotence). Sixteen wives (33%) answered affirmatively to the question about whether changes at a communicative level as a consequence of the patient's illness had occurred. In relation to the appearance of sexual changes, 46 (94%) of the wives answered affirmatively. The wives were significantly less satisfied with the relationship than the patients, which was related to communication problems. The group of patients were more satisfied with their partners than with their life, whereas no difference has been observed in the wives with both variables. An important percentage of patients with chronic insufficiency who have sexual difficulties exits. A factor which influences the perception of such problems in a very important way is the degree of affection in the relationship between the couples.